2001
DOI: 10.1101/gad.900401
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of AtRac1 by abscisic acid is essential for stomatal closure

Abstract: Plant water homeostasis is maintained by the phytohormone abscisic acid (ABA), which triggers stomatal pore closure in response to drought stress. We identified the Arabidopsis small guanosine triphosphatase (GTPase) protein AtRac1 as a central component in the ABA-mediated stomatal closure process. ABA treatment induced inactivation of AtRac GTPases and disruption of the guard cell actin cytoskeleton. In contrast, in the ABA-insensitive mutant abi1-1, which is impaired in stomatal closure, neither AtRac inact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
232
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(250 citation statements)
references
References 37 publications
16
232
0
2
Order By: Relevance
“…The enhanced ABA response of ggb guard cells is consistent with the observation that Rop6 is a negative regulator of ABA signaling in guard cells (Lemichez et al, 2001). This small GTP-binding protein has a consensus CSIL motif at its C terminus with an upstream polybasic domain, which qualifies it as a putative substrate of PGGT I. Rop2, which possesses a C-terminal CAFL motif and can be geranylgeranylated in vitro (D.N.…”
Section: Auxin Signaling In Ggb Mutant Linessupporting
confidence: 74%
See 1 more Smart Citation
“…The enhanced ABA response of ggb guard cells is consistent with the observation that Rop6 is a negative regulator of ABA signaling in guard cells (Lemichez et al, 2001). This small GTP-binding protein has a consensus CSIL motif at its C terminus with an upstream polybasic domain, which qualifies it as a putative substrate of PGGT I. Rop2, which possesses a C-terminal CAFL motif and can be geranylgeranylated in vitro (D.N.…”
Section: Auxin Signaling In Ggb Mutant Linessupporting
confidence: 74%
“…org/ptmdb/results.htm). These include eight Rop GTPases, which regulate actin organization (Fu et al, 2001(Fu et al, , 2002Gu et al, 2003), pollen tube tip growth (Lin et al, 1996;Fu et al, 2001;Gu et al, 2003), ABA and auxin signaling (Lemichez et al, 2001;Li et al, 2001;Tao et al, 2002), and other processes; AIG1, which is involved in RPS2-and avrRpt2-dependent responses to Pseudomonas infection (Reuber and Ausubel, 1996); Aux2-11, a negative regulator of auxin signaling (Wyatt et al, 1993;Caldelari et al, 2001;Dharmasiri and Estelle, 2002); and other proteins. Thus, it is surprising that era1, ggb, and plp phenotypes are not more severe.…”
Section: Auxin Signaling In Ggb Mutant Linesmentioning
confidence: 99%
“…It is then logical to infer that the magnitude of daily refilling of root xylem forms part of this hydraulic signal between roots and shoots. Our results do not preclude the interaction of hydraulic and chemical signals such as abscisic acid (Gowing, Davies & Jones 1990;Lemichez et al 2001) in governing stomatal response to variation in root embolism. The strong relationship between native k s and the daily fluctuation in Y root (Fig.…”
Section: Discussionmentioning
confidence: 71%
“…Through mutational analysis of Arabidopsi s , a number of other loci have been identified that control stomatal and other responses to ABA (e.g., ERA1 , ERA2 , ERA3 , FUS3 , LEC1 , GCA , and GPA ) (Leung and Giraudat, 1998;Schroeder et al, 2001). Most recently, unexpected loci that encode proteins involved in RNA metabolism (Hugouvieux et al, 2001;Xiong et al, 2001a) and a RHO-like GTPase (Hugouvieux et al, 2001;Lemichez et al, 2001) that controls guard cell cytoskeleton responses to ABA also have been found to mediate stomatal function. In addition, genetic loci in other species have been found to affect ABA-mediated responses, including those of stomata (Leung and Giraudat, 1998).…”
Section: Introductionmentioning
confidence: 99%